RELATIONSHIP BETWEEN ETHICAL LEADERSHIP CHARECTERISTICS OF SECONDARY SCHOOL ADMINISTRATORS AND ORGANIZATIONAL COMMITMENT OF TEACHERS - Rüyam Küçüksüleymanoğlu; Nedim Çelik (Zeitschrift für die Welt der Türken, 2014)
Educational institutions must adopt ethical values and turn these into behavior. Ethical leadership is adopting relationship based on the principles of ethical values and preceding this understanding in their institutions. In addition, it is inevitable to regard the spiritual elements providing organizational commitment of employees. In light of ethical values, the school administrators’ following a healthy method towards teachers will improve teachers’ organizational commitment. In this study, the relationship between the ethical leadership understanding of administrators who serve at secondary education institutions and the institution employees’ organizational affiliations are being examined. It’sbeing triedtocheckout the relationship between school managers’ ethical leadership understanding and application degree of this understanding in their institutions and the level of institutionemployees’ organizational commitment. Do the high school teachers’ opinions of organizational commitment show a meaningful difference according to gender, type of school, seniority, branch monthlyincome, the trade union membership of variables? Do high school teachers opinions towards the ethical leadership skills represented by school administrators, show a meaningful difference according to gender, types of school, seniority, branch monthly income ,the trade union membership of variables? Is there a relaitonship between school managers ethical leadership understanding and teachers’ organizational affilications? The sample of the study was 123 teachers working in anatolian, vocational and general high schools in Bursa. Emotional commitment scores were significantly higher than both normative scores and ongoing loyalty scores (p<0,05) and it showed that there is no difference between ongoing loyalty and normative commitment scores (p<0,05). In the research, it has been reached a conclusion that school administrators have applied a moderate leadership behavior but the teachers participating in the research with a high level of commitment to their organizations. It has also been reached a coclusion that school administrators’ ethical leadership understanding has affected teachers’ organizational commitments in different levels.